A Field‐Scale Approach to Estimate Nitrate Loading to Groundwater. Issue 4 (1st July 2018) - Malekani, Farzin; Ryan, M. Cathryn; Zebarth, Bernie J.; Loo, Shawn E.; Suchy, Martin; Cey, Edwin E.
Abstract : The quantification of groundwater NO3 loading associated with a specific field or set of management practices so that groundwater quality improvements can be objectively assessed is a major challenge. The magnitude and timing of NO3 export from a single agricultural field under raspberry ( Rubus idaeus L.) production were investigated by combining high‐resolution groundwater NO3 concentration profiles (sampled using passive diffusion samplers) with Darcy's flux estimation at the field's down‐gradient edge (based on field‐measured hydraulic gradients and laboratory‐estimated hydraulic conductivity). Annual recharge estimated using Darcy's law (1002 mm) was similar to that obtained using two other approaches. The similarity in the rate of Cl applied to the field and the estimated export flux over the 1‐yr monitoring period (51 vs. 56 kg Cl ha −1 ) suggested the mass flux estimation approach was robust. An estimated 80 kg NO3 –N ha −1 was exported from the agricultural field over the 1‐yr monitoring period. The greatest monthly groundwater mass flux exported was observed in February and March (∼11 kg NO3 –N ha −1 ), and was associated with NO3 leached from the soil zone during the onset of precipitation in the previous autumn. Provided the groundwater recharged from the field of interest can be isolated within a vertical profile, this approach is an effective method for obtaining spatially integrated estimates of the magnitude and timing of NO3 − loading to groundwater. Core Ideas: High‐resolution groundwater monitoring was used with Darcy flux estimation. The recharge estimate was comparable with two other methods. This approach accurately estimated loading of Cl tracer. Nitrate loading exported from individual field was quantified on a seasonal basis. This approach is appropriate for agricultural fields over vulnerable aquifers.